The effect of combined cognitive-behavioral psychoeducation and music intervention on stress, self-efficacy, and relapse rates in patients with alcohol and substance use disorders: A randomized controlled trial - Kayaoglu, Kubra; Altun, Ozlem Sahin (Wiley, 2022)
Purpose This study was conducted to determine the effect of psychoeducation and music intervention on stress, self-efficacy, and relapse rates in alcohol and substance use disorders. Design and Methods This was a randomized controlled study. The study sample included 62 patients who met the inclusion criteria. For 3 weeks, the patients in the experimental group received eight sessions of psychoeducation and music intervention. Findings The total mean Self-Efficacy Scale score of the participants in the experimental group significantly increased as compared with that of the control group. The experimental group's total mean Perceived Stress Scale score and relapse rate significantly decreased compared to that of the control group. Practice Implications Psychoeducation and music intervention effectively reduced stress, increased self-efficacy, and prevented relapses.
Keywords: cognitive behavioral therapy; music; nursing; self-efficacy; substance use disorders